Comparison of lipid extraction methods for the microalgae Acutodesmus obliquus - Hurtado, Diana Ximena; Garzón-Castro, Claudia Lorena; Cortes-Romero, Jhon; Tello, Edisson (International Journal of Agricultural and Biological Engineering, 2018)
Microalgae are widely used in the pharmaceutical and energy industries, therefore the conditions for their cultivation and extraction methods play an important role in the profiling and acquisition of lipids. The efficiency of lipid extraction from microalgae has attracted great interest from industry because of the wide variety of lipids and amounts that can be obtained. Acutodesmus obliquus (Scenedesmus obliquus UTEX 393) was used in this study. It was cultivated in Bold 3N medium modified with 75% nitrogen at 25°C, pH 6.8, 125 r/min and a photoperiod of 18/6 h and illuminated with white light provided by a Light-Emitting Diode Surface Mount Device extensions (LED SMD) with an intensity of 1200 µE/(m2•s). The cells were stained with the Red Nile (RN) technique to indicate lipid production. Four extraction methods were compared, classical, microwave (MW), Soxhlet, and ultrasound (US), using the same solvent proportions (hexane: chloroform: methanol=1:2:3). All samples were analyzed with Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography coupled to Mass Spectrometry (GC-MS). The results showed: 1) lipid production detected by RN was consistent with microalgal growth; 2) the MW technique was the best extraction method, according to the statistical analysis through Randomized Complete Block (RCB) design and performance of 4.6%; and 3) the presence of saturated and unsaturated acids was indicated by FTIR spectra. GC-MS was able to identify palmitic and linoleic acids as the likely major constituents of the sample.Keywords: Acutodesmus obliquus, lipid extraction, trans-esterification, Red Nile (RN)DOI: 10.25165/j.ijabe.20181105.3748Citation: Hurtado D X, Garzón-Castro C L, Cortés-Romero J, Tello E. Comparison of lipid extraction methods for the microalgae Acutodesmus obliquus. Int J Agric & Biol Eng, 2018; 11(5): 211–217.